2022
DOI: 10.1093/ofid/ofac515
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnoses in the Context of Suspected Pandemic Influenza or Coronavirus Disease 2019: A Systematic Review

Abstract: There have been numerous reports of patients initially misdiagnosed in the H1N1 and COVID-19 pandemics within the literature. A systematic review was undertaken to collate misdiagnoses during the H1N1/2009 and COVID-19 pandemics and identify which cognitive biases may contribute to this. MEDLINE, Embase, Cochrane and MedRxiv databases were searched for misdiagnoses or cognitive biases resulting in misdiagnosis, occurring during the H1N1/2009 or COVID-19 virus pandemics. Eligible studies were quality assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Misdiagnosis has been reported not only during the COVID-19 pandemic but also during the 2009 H1N1 influenza pandemic. Lucy et al reviewed 16 eligible studies and identified 686 misdiagnoses with 97 final diagnoses [ 6 ]. In their systematic review, respiratory infections accounted for the majority (72%), and nonrespiratory infections (14%) and noninfectious diseases accounted for the remainder (14%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misdiagnosis has been reported not only during the COVID-19 pandemic but also during the 2009 H1N1 influenza pandemic. Lucy et al reviewed 16 eligible studies and identified 686 misdiagnoses with 97 final diagnoses [ 6 ]. In their systematic review, respiratory infections accounted for the majority (72%), and nonrespiratory infections (14%) and noninfectious diseases accounted for the remainder (14%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cases that were initially misdiagnosed during the COVID-19 pandemic have been reported. Cognitive biases such as anchoring or premature closure have been shown to contribute to these misdiagnoses in some cases [ 6 ]. Diagnostic errors caused by cognitive biases during the pandemic could lead to fatal outcomes in patients with malaria because Plasmodium falciparum malaria needs to be diagnosed and treated as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 represents one of the most important diseases nowadays, it must not mask other diseases that may have another type of therapeutic management [73]. Misdiagnosis during the COVID-19 pandemic has become highly frequent; several infectious diseases and chronic non-communicable diseases have been reported to be misdiagnosed with COVID-19, mainly when the clinical presentation had an atypical course [74]. Misdiagnosis occurs mainly with other etiologies that cause respiratory compromise, like several mycoses and bacterial infections, among others; however, it is possible that other non-specific infectious diseases might be misdiagnosed as COVID-19 [75,76].…”
Section: N Discussionmentioning
confidence: 99%